Gender Patterns in Indonesian: A Corpus Study of Personal Pronoun References “Ia” and “Dia” - Hernina; Karlina, Yenny; Puspitasari, Devi Ambarwati (Center of Language Development, Institut Agama Islam Negeri Madura, 2024)
Indonesian is a language that does not have a grammatical gender feature, and this absence extends to the third-person singular pronouns. In English and many European languages, there are distinct second-person for addressing genders: male and female. The grammatical structure of Indonesian remains unchanged despite temporal shifts and the absence of gender-specific distinctions. The official Indonesian dictionary (Kamus Besar Bahasa Indonesia or KBBI) does not designate ia and dia with explicit gender distinctions, such as masculine and feminine. This research aims to discuss the masculine and feminine contextual patterns of the pronouns ia and dia within the Indonesian Corpus (Korpus Bahasa Indonesia or KOIN). The study used a dataset comprising 121.098 tokens selected from literature, national, and social categories. Identifying gender patterns in using the second-person pronouns gets the research focus on the data of 19.697 concordances of the word ia and 10.031 concordances of dia. The findings indicate that dia has a reasonably equal association with both genders, but the word ia prefers feminine references more. It clarifies the nuances of gender expression in Indonesian and explains how linguistic decisions communicate gender information.